GAME-BASED LEARNING (GBL) AND TRADITIONAL TEACHING METHODS IN ENHANCING ENGLISH GRAMMAR RETENTION - Suci Ramadhani, Andi; Anwar Korompot, Chairil; Rayhana Sofyan, Ryan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to compare the effectiveness of Game-Based Learning (GBL) and Traditional Teaching Methods (TTM) in enhancing English grammar retention among eighth-grade students at SMP Negeri 1 Makassar. A quantitative approach with a quasi-experimental design was employed, specifically the Non-equivalent Control Group Design. The sample consisted of 79 students selected through random cluster sampling: 42 students in the experimental group (VIII.5) and 37 students in the control group (VIII.6). Data were collected through pre-tests and delayed post-tests administered two weeks after the intervention.and analyzed using descriptive statistics and independent-samples t-tests. The findings revealed that both methods contributed positively to students' grammar retention; however, Game-Based Learning produced significantly greater improvement. The experimental group's mean score increased from 37.26 to 74.17, compared to the control group's increase from 34.32 to 60.68. The independent-samples t-test yielded a significant difference (t = 3.280, p = 0.002 < 0.05), indicating that Game-Based Learning produced significantly greater improvement than Traditional Teaching Methods in enhancing grammar retention. The superior outcomes of the GBL group were attributed to the interactive, student-centered, and engaging nature of game-based activities implemented through the Baamboozle platform, which fostered motivation, active participation, and repeated contextual grammar practice. It is concluded that Game-Based Learning is more effective than Traditional Teaching Methods in enhancing English grammar retention among junior high school students.